2021
DOI: 10.1155/2021/5560310
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Gut Microbiota and Metabolites in Pathogenesis of Functional Constipation

Abstract: Functional constipation (FC), a condition characterized by heterogeneous symptoms (infrequent bowel movements, hard stools, excessive straining, or a sense of incomplete evacuation), is prevalent over the world. It is a multifactorial disorder and can be categorized into four subgroups according to different pathological mechanisms: normal transit constipation (NTC), slow transit constipation (STC), defecatory disorders (DD), and mixed type. Recently, growing evidence from human and animals has pointed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 127 publications
(173 reference statements)
1
33
0
Order By: Relevance
“…In IBS patients, the physiological manifestations are closely related to neurotransmitters, including abnormal gastrointestinal motility, visceral sensory abnormalities, central sensory abnormalities, anxiety, and depression ( 68 ). Changes in microbial composition and metabolomics are related to the abnormality in neurotransmitter expression in the system, and would also influence the intestinal neuronal pathways that control intestinal sensorimotor function ( 69 , 70 ) These neurotransmitters not only regulate blood flow, but also influence intestinal movement, the absorption of nutrients, natural immunity of the gastrointestinal system, and the microbiota. Therefore, the pathways and mechanisms that are involved in neurotransmitter synthesis, as well as neuron inactivation, could serve as potential targets for therapeutic drugs for psychiatric and neurological diseases because they play such an important role in brain function.development ( 71 ).…”
Section: Neurotransmittersmentioning
confidence: 99%
“…In IBS patients, the physiological manifestations are closely related to neurotransmitters, including abnormal gastrointestinal motility, visceral sensory abnormalities, central sensory abnormalities, anxiety, and depression ( 68 ). Changes in microbial composition and metabolomics are related to the abnormality in neurotransmitter expression in the system, and would also influence the intestinal neuronal pathways that control intestinal sensorimotor function ( 69 , 70 ) These neurotransmitters not only regulate blood flow, but also influence intestinal movement, the absorption of nutrients, natural immunity of the gastrointestinal system, and the microbiota. Therefore, the pathways and mechanisms that are involved in neurotransmitter synthesis, as well as neuron inactivation, could serve as potential targets for therapeutic drugs for psychiatric and neurological diseases because they play such an important role in brain function.development ( 71 ).…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Notably, the gut microbiota is another potential mechanism that affects the rectal sensitivity in patients with FC. Previous studies reported a decrease in beneficial bacteria such as Lactobacillus, an increase in harmful bacteria, and a reduction in species richness in FC patients (Wang and Yao, 2021). Colonic functions could be modulated by gut microbiota via the metabolites of bacterial fermentation, which could trigger the release of gut hormones.…”
Section: Discussionmentioning
confidence: 94%
“…Intestinal nerve parameters that promote intestinal motility and the transport of contents are secreted by intestinal neural networks in the gastrointestinal tract ( 31 ). Gastrointestinal hormones are small-molecule peptides, some of which also exist in the central nervous system, so they are also referred to as brain-gut peptides or neurotransmitters ( 32 – 34 ). After binding to receptors on target cells, gastrointestinal hormones play important regulatory roles in the absorption, movement, secretion, and immune health of the digestive system through different signaling mechanisms, some of which are closely related to constipation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%